First description of the male spider Pacifiphantes magnificus (Chamberlin & Ivie) (Araneae: Linyphiidae) - Slowik, Jozef; Blagoev, Gergin A. (Zootaxa, 2012)
The spider Pacifiphantes magnificus (Chamberlin & Ivie 1943)(Linyphiidae), originally described as a member of the ge-nus Bathyphates, is redescribed and the first description of the male is presented. DNA barcoding was used to test the conspecificity of specimens from different collection events and to help match specimens from different sexes.